Anosognosia in patients with Alzheimer's disease: current perspectives. Issue 3 (12th January 2020) - Tagai, Kenji; Nagata, Tomoyuki; Shinagawa, Shunichiro; Shigeta, Masahiro
Abstract : Alzheimerʼs disease (AD) is a neurodegenerative disease characterised by neurocognitive impairments, especially memory impairment, as core symptoms linked to reductions in activities of daily life. As marginal symptoms, neuropsychiatric symptoms (NPSs) appear during the progressive course of the disease. A lack of self‐awareness (anosognosia) of cognitive and functional impairments is often seen in patients with AD, and associations between anosognosia and other NPSs have been previously reported. To account for anosognosia pathogenesis neurocognitively, the cognitive awareness model (CAM) has been helpful for explaining the stream of events from sensory input to behavioural/affective and metacognitive outputs. According to CAM, there are three types of anosognosia: (i) primary anosognosia, (ii) executive anosognosia, and (iii) mnemonic anosognosia. These types of anosognosia are generated from different neurocognitive modulations leading to metacognitive outputs or behavioural/affective regulations. Primary anosognosia is considered to be caused by deficits in the metacognitive awareness system (MAS). While preserved MAS function is associated with milder depression and anxiety in AD, a severer depressive mood in patients with mild AD can inversely cause self‐underestimation. The modulation of executive anosognosia is thought to be associated with dangerous/disinhibition behaviours and apathy among NPS sub‐symptoms, via impairments of comparator mechanism (Cm) within the central executive system. Other neurobehavioral reactions linked to self‐awareness include 'denying' and 'confabulation', and each of these reactions is thought to be affected by the MAS and a Cm. Denial of oneʼs own memory impairments appears as a defensive reaction to protect against dysphoric feelings, and the confabulatory comment is instantly reaction constructed by fabrications according to misinterpretations of memory information about oneself. Similarly, the innovative development of a theoretical model (CAM) has contributed to explaining the mechanism of anosognosia and some neurobehavioral outputs from a neurocognitive perspective.